Persistence and Success of Student Mobilization in a Post-Dictatorship and Neoliberal Context in Chile (1990-2020) - Bellei, Cristián; Villalobos, Cristóbal (International Higher Education, 2024)
<h3 id="chilean-education-is-known-as-a-market-driven-segregated-and-highly-privatized-system-these-characteristics-have-generated-a-complete-reconfiguration-of-the-higher-education-system-which-is-experienced-by-students-as-inequitable-and-unfair-the-student-movement-has-been-a-key-actor-in-responding-to-this-system-through-constant-and-often-massive-protests-over-the-past-30-years-it-has-been-especially-during-the-last-three-governments" data-pm-slice="1 1 []">Chilean education is known as a market-driven, segregated, and highly privatized system. These characteristics have generated a complete reconfiguration of the higher education system, which is experienced by students as inequitable and unfair. The student movement has been a key actor in responding to this system through constant and often massive protests over the past 30 years. It has been especially during the last three governments.